2020
DOI: 10.1039/d0ra01396j
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensivein silicomodeling of the rice plant PRR Xa21 and its interaction with RaxX21-sY and OsSERK2

Abstract: This study exhausts bioinformatics tools to acquire the entire multi-domain rice Xa21 protein structure and analyzes its interactions with its PAMP RaxX21-sY and co-receptor OsSERK2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 106 publications
2
10
0
Order By: Relevance
“…However, the solvent-exposed residues, x, are assumed to be associated with ligand binding. e predicted 3D structure of RLK7 is similar to other similar RLKs available [40][41][42][43][44][45].…”
Section: Structural Elucidation Of Rlk7supporting
confidence: 68%
See 1 more Smart Citation
“…However, the solvent-exposed residues, x, are assumed to be associated with ligand binding. e predicted 3D structure of RLK7 is similar to other similar RLKs available [40][41][42][43][44][45].…”
Section: Structural Elucidation Of Rlk7supporting
confidence: 68%
“…e extracellular LRR domain of RLK7 is distinguished by the consensus sequence LxxLxLxxNxLxx (Figure 2), which matches well with other RLK-LRR consensus sequences found in Arabidopsis [20]. With our previously developed multipletemplate modeling approach, namely, HHpred [39,40], the top five templates (4Z5W_A, 5IXO_A, 4MNA_A, 4LXR_A, and 5JFK_A) were selected and then used to predict the 3D structure of RLK7 ectodomain (Figure 3).…”
Section: Structural Elucidation Of Rlk7supporting
confidence: 55%
“…PROCHECK Ramachandran plot of the rice Xa21 protein model generated by the HHpred server showed that 99.2% of residues in the model were in the allowed region (78.9% in the most favored, 18.4% in the additionally allowed, 1.9% in generously allowed and 0.8% in disallowed regions). The model generated by PHYRE2 for the same protein had 4% less residues in the most favored regions [ 40 ]. Similar results were described for rice cytokinin oxidase/dehydrogenase 2 (CKX2) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lys164 of OsSERK2 interacts with Asp565 of Xa21 by forming an ionic bond within 4Å (Fig. 2c) (Mubassir et al, 2020). S2).…”
Section: Changes In Interactions Of Prominent Residues Of the Proteinsmentioning
confidence: 99%